Incidence of Abnormal FDG-PET in Partial Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Forty children were studied with EEG, MRI, and F-fluorodeoxyglucose (FDG)-PET, within one year of their third unprovoked partial seizure, at the Children's National Medical Center, George Washington University School of Medicine, Washington, DC.